Sociodemographic, biological, and psychosocial correlates of light- and moderate-to-vigorous-intensity physical activity during school time, recesses, and physical education classes - Bruno G.G. da Costa; Kelly S. da Silva; Jaqueline A. da Silva; Giseli Minatto; Luiz R.A. de Lima; Edio L. Petroski (Elsevier, 2019)
Background: Identifying factors associated with physical activity (PA) is useful in planning interventions and policies. The aim of this study was to identify sociodemographic, biological, and psychosocial factors associated with PA performed in school settings. Methods: Data collected for the present study included gender, age, socioeconomic status, body fat percentage, aerobic fitness, self-efficacy, attitudes, peer and parental support, and perception of school environment. Dependent variables were light-intensity PA (LPA) and moderate-to-vigorous-intensity PA (MVPA) performed during school time, recesses, and physical education (PE) classes. Multiple regression analyses were performed. Results: Participating adolescents (n = 567, 53% female, 12.9 ± 5.3 years) spent 5% of school time in MVPA and 27% in LPA, 15% of recesses in MVPA and 44% in LPA, and 16% of PE classes in MVPA and 41% in LPA. Boys engaged in more MVPA in all categories. Age was inversely related with MVPA and LPA in all periods, whereas body fat percentage was inversely related with MVPA in school time and PE classes. Attitude was inversely related with MVPA in all periods and with LPA in recesses. Considering PA to be good and enjoyable was positively associated with MVPA in school time. Conclusion: Adolescents spent little time in PA during school. Future interventions should implement enjoyable activities at school. Keywords: Accelerometer, Adolescents, Attitude, Physical education, Public health, Self-efficacy